2018
DOI: 10.1016/j.tjog.2017.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic en bloc resection of a para-cervical cancer with OHVIRA syndrome

Abstract: In the case of cervical carcinoma with OHVIRA syndrome, laparoscopic surgery is preferable for the diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…In contrast, our results suggest that genitourinary anomalies are linked to an increased risk of adenocarcinoma, although our sample size was too small to draw definitive conclusions. Consistent with our results, Kusunoki and colleagues reported a case of cervical clear cell carcinoma with OHVIRA syndrome, who had no in-utero DES exposure 29.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, our results suggest that genitourinary anomalies are linked to an increased risk of adenocarcinoma, although our sample size was too small to draw definitive conclusions. Consistent with our results, Kusunoki and colleagues reported a case of cervical clear cell carcinoma with OHVIRA syndrome, who had no in-utero DES exposure 29.…”
Section: Discussionsupporting
confidence: 92%
“…They posited that the link between teratogenesis and oncogenesis exemplified Knudson's two-hit theory of carcinogenesis 32. Carcinogenesis of clear cell carcinoma from Müllerian anomaly is considered, that clear cell carcinoma may have arisen from the paracervix of Müllerian-derived columnar epithelium that have persisted for a long time and was subjected to genetic and hormonal changes 29. Our findings support their hypothesis that the teratogenic effect combined with cancer genetic susceptibility inordinately predisposes patients to the “second hit”, resulting in genital tract carcinomas or even multiple primary malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer in uterus didelphys is an extremely rare occurrence, and there have been very few reports. We found four case reports, including five patients with OHVIRA syndrome associated with cervical cancer ( Cordoba et al, 2017 , Kaba et al, 2013 , Kusunoki et al, 2018 , Watanabe et al, 2012 ). We compared several points in six cases, including ours ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are two hypotheses regarding the association between adenocarcinoma and Müllerian duct anomalies. One hypothesis is that the tumor may have arisen from the paracervix of Müllerian-derived columnar epithelium subjected to genetic and hormonal changes for an extended period of time ( Kusunoki et al, 2018 ). The second hypothesis is that it arises from endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report a case of CCAC in UD associated with URA treated with radical intensitymodulated radiotherapy (IMRT) and high-dose rate intracavitary brachytherapy (HDR-ICBT) at the National Cancer Center/Cancer Hospital (Beijing, China) between December 2016 and June 2017. The patient's medical records were retrospectively reviewed, and we also carried out a comprehensive review of seven cases with this rare joint condition reported in the literature (4)(5)(6)(7)(8). Clinicopathologic features, treatments, and outcomes for the eight cases are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%